Human diet and nutrition in biocultural perspective : past meets present - Moffat, Tina, 1967-; Prowse, Tracy Lynn (Studies of the Biosocial Society, 2010)
There are not many areas that are more rooted in both the biological and social-cultural aspects of humanking than diet and nutrition. Throughout human history nutrition has been shaped by political, economic, and cultural forces, and in turn, access to food and nutrition has altered the course and direction of human societies. Using a biocultural approach, the contributors to this volume investigate the ways in which food is both an essential resource fundamental to human health and an expression of human culture and society. The chapters deal with aspects of diet and human nutrition through space and time and span prehistoric, historic, and contemporary societies spread over various geographical regions, including Europe, North America, Africa, and Asia to highlight how biology and culture are inextricably linked. --Book Jacket.